Progress in greywater reuse for home gardening: Opportunities, perceptions and challenges. (April 2020) - Radingoana, Makgalake P.; Dube, Timothy; Mazvimavi, Dominic
Abstract: Water is one of the most essential natural resource that sustains livelihoods. Freshwater consumption and demand have, spiralled over the years, due to population growth, agricultural and industrial intensification. Innovative water conservation techniques (greywater reuse, rainwater harvesting, seawater desalination and ground water extraction, etc.), especially in the face of climate change and climate variability are central in minimizing water shortages, hunger and poverty alleviation, as well as health challenges. Most of water conservation methods remain ineffective and have less adoption, due to associated costs, inaccessibility and technical expertise in addressing water challenges, particularly in developing countries. Greywater reuse, which approximately represents 43–70% of the total domestic wastewater volume remains as the alternative and effective source of water that can help reduce pressure on freshwater for food production and poverty alleviation in third-world countries. Great research strides have been demonstrated on greywater reuse for agricultural use, but much remains unknown with regard to adoption rates, especially in developing countries. This work provides a detailed review on greywater reuse in crop production with particular emphasis on community perceptions, challenges and opportunities, lessons from other countries and possible implications on food security. The study has demonstrated that greywater reuse is a common practice in both developed and developing nations as a coping strategy. However, it was observed that some communities remain cautious and sceptic on its use for home gardening purpose. This resource is regarded as unclean and unfit for food crop irrigation. Limited adoption rates seem to be due to limited information or awareness programs and platforms on the potential of greywater reuse as supplement for freshwater, especially in developing countries like South Africa. However, strategies i.e. installation of greywater systems, incentivising greywater use have seen a rise in the adoption greywater in developed world. There is a need to find possible ways on how strategies from developed countries can be adopted in developing countries to promote greywater reuse for home gardening purposes. Highlights: Climate change contributes towards the reduction in the availability of water resources. Greywater has a potential to can supplement freshwater in agriculture. People's perceptions towards greywater play a major role in its reuse. Greywater reuse has a potential to improve food security in arid and semi-arid third-world countries. Some challenges associated with greywater reuse particularly on the receiving environment are still under-researched.